2010
DOI: 10.1103/physreve.82.031111
|View full text |Cite
|
Sign up to set email alerts
|

Temperature for a dynamic spin ensemble

Abstract: In molecular dynamics simulations, temperature is evaluated, via the equipartition principle, by computing the mean kinetic energy of atoms. There is no similar recipe yet for evaluating temperature of a dynamic system of interacting spins. By solving semiclassical Langevin spin-dynamics equations, and applying the fluctuation-dissipation theorem, we derive an equation for the temperature of a spin ensemble, expressed in terms of dynamic spin variables. The fact that definitions for the kinetic and spin temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 33 publications
5
79
0
Order By: Relevance
“…The local lattice temperature T l and the local spin temperature T s are evaluated using the equipartition principle and Eq. (27). The temperature of the electrons T e is a spatially varying local quantity, the evolution of which is described by the heat transfer equation.…”
Section: A Equations Of Motion For the Coupled Subsystemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The local lattice temperature T l and the local spin temperature T s are evaluated using the equipartition principle and Eq. (27). The temperature of the electrons T e is a spatially varying local quantity, the evolution of which is described by the heat transfer equation.…”
Section: A Equations Of Motion For the Coupled Subsystemsmentioning
confidence: 99%
“…We evaluate its ensemble average by using the FurutsuNovikov theorem, [53][54][55][56][57] similarly to how it was done in Ref. 27. The ensemble-average value of the second term is evaluated using the equipartition principle.…”
Section: A Spatially Homogeneous Casementioning
confidence: 99%
See 1 more Smart Citation
“…13,14 In this formalism, the spin and lattice degrees of freedom are coupled by the exchange integral term, in the sense that the lattice degree of freedom would change the behavior of the spin degree of freedom, and vice versa. The SLD formalism is thus suited for spin-carrying materials, such as iron.…”
Section: Spin-lattice Dynamicsmentioning
confidence: 99%
“…The method of TI has been applied to study the vacancy formation and migration occurring in BCC iron, 18,19 whose Hamiltonian is modeled by the SLD formalism. 13,14 The study uses the SLD formalism to determine the free energy change in the course of vacancy formation and migration by TI. By using both magnetic and nonmagnetic potentials, it is found that a vacancy leads to scattering of magnons, leading to an increase in the total free energy.…”
Section: Thermodynamic Integrationmentioning
confidence: 99%